2015
DOI: 10.1186/s13041-014-0092-8
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase receptor type R is required for Purkinje cell responsiveness in cerebellar long-term depression

Abstract: BackgroundRegulation of synaptic connectivity, including long-term depression (LTD), allows proper tuning of cellular signalling processes within brain circuitry. In the cerebellum, a key centre for motor coordination, a positive feedback loop that includes mitogen-activated protein kinases (MAPKs) is required for proper temporal control of LTD at cerebellar Purkinje cell synapses. Here we report that the tyrosine-specific MAPK-phosphatase PTPRR plays a role in coordinating the activity of this regulatory loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 67 publications
3
64
0
Order By: Relevance
“…We thus asked whether neuronal AKHR was also required for starvation-induced increase in food consumption. We first examined food consumption during the course of a single meal, by using a capillary-based feeding assay named the MAFE ( MA nual FE eding) assay ( Qi et al, 2015 ) ( Figure 3d ). We found that starvation could significantly increase food consumption, and that neuronal knock-down of AKHR did not affect starvation-induced increase in meal size ( Figure 3f ).…”
Section: Resultsmentioning
confidence: 99%
“…We thus asked whether neuronal AKHR was also required for starvation-induced increase in food consumption. We first examined food consumption during the course of a single meal, by using a capillary-based feeding assay named the MAFE ( MA nual FE eding) assay ( Qi et al, 2015 ) ( Figure 3d ). We found that starvation could significantly increase food consumption, and that neuronal knock-down of AKHR did not affect starvation-induced increase in meal size ( Figure 3f ).…”
Section: Resultsmentioning
confidence: 99%
“…It has also appeared difficult to study each step independently, many studies focusing on the global cytotoxicity resulting from aggregates internalization 16 20 27 31 . The binding step can be studied in vitro using artificial liposomes 11 22 32 33 34 , but this strategy neglects the prominent role of membrane proteins and the extracellular matrix in fibrils binding 10 13 17 35 . In this work we demonstrate, by measuring the binding of fibrils displaying identical structures and physico-chemical properties but different lengths to lipid vesicles and cultured cells, that fibril ends are not a prime determinant of the binding process of αSyn and HTTExon1 assemblies.…”
Section: Discussionmentioning
confidence: 99%
“…Different mechanisms have been proposed. The binding could be passive 10 , mediated by an interaction with the membrane lipids 11 , and/or with specific protein partners 12 13 14 . The efficiency of the binding seems to depend both on the aggregates characteristics, such as their charge or conformation 10 15 , and on the properties of the membrane, with an emphasis on the role of a specific lipid composition 16 17 or of the membrane curvature 18 19 .…”
mentioning
confidence: 99%
“…On the postsynaptic side, the endosomal system is involved in the insertion of integral neurotransmitter receptors in the plasma membrane, which is a mechanism of synaptic plasticity (see review 18 ). For example, depletion of the endosomal sorting protein VPS35 leads to decreased levels of glutamate receptors in the plasma membrane, reducing glutamatergic neurotransmission 19 21 . The glutamate ionotropic receptor AMPA type subunit 1 (gene GRIA1, Supplementary Table S2 , Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%